The UN has failed in its mission to secure global peace and defend global citizens - Levy, Moira (New Agenda: South African Journal of Social and Economic Policy, 2024)
The United Nations has clearly failed to uphold even the very first line of its founding Charter, which commits the nations of the world to “save succeeding generations from the scourge of war”, and has shown itself to be entirely ineffective against genocide in Gaza, civil war in Sudan and Congo, bloody assaults by Russia on its neighbour, Ukraine, and hostilities in the Middle East that raise the spectre of a inconceivably disastrous Third World War.